Analisis Perancangan Tata Letak Pabrik Kopi Java Preanger Gunung Tilu Menggunakan Metode Activity Relationship Chart (ARC) - Aji, Bagas Abiyoga Hastyo; Irjayanti, Maya (Accounting Undergraduate (S1) and Diploma Study Program (D3), STIE EKUITAS, 2023)
Layout design is important in managing material flow, productivity and human relations within the factory. There are 8 work stations at the Java Preanger Gunung Tilu Coffee Factory, namely warehouse, weighing, washing, pulping machines, huller machines, sorting and roasting machines. This study aims to determine the initial layout of the factory and to compare the initial layout with the proposed layout using descriptive methods with the Activity Relationship Chart (ARC) method, which shows the importance of whether or not a department should be approached in order to create company work efficiency. Then a comparison is made between the mileage of the initial layout and the proposed layout. The results showed that the production process flow was irregular because the distances were not suitable and far apart and the total displacement was 43,808.4 meters. By applying the Activity Relationship Chart (ARC) method, several parts of the factory experienced a change in position which resulted in a proposed layout with reduced mileage during the production process from 61.6 meters to 43.5 meters and the number of displacements reduced to 31,271.5 meters